The Small Molecule Alpha-Synuclein Aggregator, FN075, Enhances Alpha-Synuclein Pathology in Subclinical AAV Rat Models - Rachel Kelly; Andrew G. Cairns; Jörgen Ådén; Fredrik Almqvist; Alexis-Pierre Bemelmans; Emmanuel Brouillet; Tommy Patton; Declan P. McKernan; Eilís Dowd (Biomolecules, 2021)
Animal models of Parkinson’s disease, in which the human α-synuclein transgene is overexpressed in the nigrostriatal pathway using viral vectors, are widely considered to be the most relevant models of the human condition. However, although highly valid, these models have major limitations related to reliability and variability, with many animals exhibiting pronounced α-synuclein expression failing to demonstrate nigrostriatal neurodegeneration or motor dysfunction. Therefore, the aim of this study was to determine if sequential intra-nigral administration of AAV-α-synuclein followed by the small α-synuclein aggregating molecule, FN075, would enhance or precipitate the associated α-synucleinopathy, nigrostriatal pathology and motor dysfunction in subclinical models. Rats were given unilateral intra-nigral injections of AAV-α-synuclein (either wild-type or A53T mutant) followed four weeks later by a unilateral intra-nigral injection of FN075, after which they underwent behavioral testing for lateralized motor functionality until they were sacrificed for immunohistological assessment at 20 weeks after AAV administration. In line with expectations, both of the AAV vectors induced widespread overexpression of human α-synuclein in the substantia nigra and striatum. Sequential administration of FN075 significantly enhanced the α-synuclein pathology with increased density and accumulation of the pathological form of the protein phosphorylated at serine 129 (pS129-α-synuclein). However, despite this enhanced α-synuclein pathology, FN075 did not precipitate nigrostriatal degeneration or motor dysfunction in these subclinical AAV models. In conclusion, FN075 holds significant promise as an approach to enhancing the α-synuclein pathology in viral overexpression models, but further studies are required to determine if alternative administration regimes for this molecule could improve the reliability and variability in these models.